Acoustic Emissions from Grey Glacier, Chilean Patagonia: dataset of infrasound measurements - Sanchez, Claudia; Gheri, Duccio; Casanova, Edgardo; Zuccarello, Luciano; De Angelis, Silvio; Marchetti, Emanuele (My University, 2025)
Calving is a critical process contributing to ice mass loss in tidewater and lake-terminating glaciers, with significant implications for freshwater input, glacier dynamics, and climate change. Infrasound emissions generated by calving events represent a powerful tool for monitoring, quantifying, and understanding the mechanisms that drive glacier retreat. In this study, we present the first acoustic dataset collected over a six-day period during the austral summer at Grey Glacier, located in Torres del Paine National Park, Chile. We provide a detailed description of the instrumentation setup, data acquisition procedures, and signal processing methodologies. By applying high-sensitivity infrasound array processing techniques, we demonstrate that coherent signals generated by calving events can be reliably extracted from the acoustic data, despite environmental conditions, such as strong winds that affect infrasound propagation. This dataset represents a valuable resource for advancing research on cryosphere dynamics and offers practical applications for the glaciological and geophysical communities.
Keywords: Infrasound; Glacier; Geology; Environmental science; Oceanography; Geography; Physical geography; Acoustics; Physics